Frontliners - Pitcher, Fiona (London : BBC Training Videos, 1990)
There are three volumes in this series called Frontliners who are a supervisor or organiser of the workplace. Frontliners is a series of videos and working notes which aims to'unlock' that potential and enable everybody to increase their awareness of the critical frontliners role.
vol. 1. You and your workplace - vol. 2. You and your organisation - vol. 3. You and your product
Videos are accompanied by three books of training notes
Keywords: Personnel management; Executives; Management